A novel genome-wide in vivo screen for metastatic suppressors in human colon cancer identifies the positive WNT-TCF pathway modulators TMED3 and SOX12 - Duquet, Arnaud (BlackWell Publishing Ltd, 2014)
The progression of tumors to the metastatic state involves the loss of metastatic suppressor functions. Finding these, however, is difficult as in vitro assays do not fully predict metastatic behavior, and the majority of studies have used cloned cell lines, which do not reflect primary tumor heterogeneity. Here, we have designed a novel genome-wide screen to identify metastatic suppressors using primary human tumor cells in mice, which allows saturation screens. Using this unbiased approach, we have tested the hypothesis that endogenous colon cancer metastatic suppressors affect WNT-TCF signaling. Our screen has identified two novel metastatic suppressors: TMED3 and SOX12, the knockdown of which increases metastatic growth after direct seeding. Moreover, both modify the type of self-renewing spheroids, but only knockdown of TMED3 also induces spheroid cell spreading and lung metastases from a subcutaneous xenograft. Importantly, whereas TMED3 and SOX12 belong to different families involved in protein secretion and transcriptional regulation, both promote endogenous WNT-TCF activity. Treatments for advanced or metastatic colon cancer may thus not benefit from WNT blockers, and these may promote a worse outcome.